A nonlinear equation for fluids in multiconnected domain - Marin, Marin; Agarwal, Ravi P; Florea, Olivia A (Springer Science and Business Media LLC, 2015)
In this paper we propose a mathematical model for Reynolds' equation of a compressible fluid on a multiconnected field which simulates the function of a hybrid bearing. The boundary conditions on the inner boundaries are derived from the flow-rate continuity through the supplying orifices and are expressed by means of an integro-differential nonlinear equation. We propose a numerical method to solve this mathematical model.